The Effectiveness Test of Biofertilizer Phosphate-Solubilizing Bacteria (PSB) and Phosphate Fertilizer on The P availability in the Soil and Tomato Plant Tissue - Sari, Retno Purnama Sari; Tri Candra Setiawati; Bambang Hermiyanto (University of Jember, 2024)
Phosphorus is one of the essential nutrients whose availability is very small in the soil. Research on the effectiveness test of biofertilizer phosphate solubilizing bacteria (PSB) and phosphate fertilizer (SP-36 and rock phosphate) on the availability of soil p and p content in tomato plant tissue to determine the effectiveness of SP-36, Rock Phosphate and PSB in increasing P availability soil. The study used factorial randomized block design with two factors and three replications. The first factor is a phosphate solvent bacterial isolate consisting of two levels, without isolate Pseudomonas sp. and with Pseudomonas sp. The second factor is phosphate fertilizer with five levels of control; SP-36 fertilizer 0.32 g/plant; SP-36 fertilizer 0.63 g/plant; rock phosphate fertilizer 0.41 g/plant; and rock phosphate fertilizer 0.81 g/plant. The data obtained were analyzed using Analysis of Variety and continued with Duncan Multiple Range Test (DMRT) test with 95% confidence level. The results showed that the administration of PSB isolate gave increased P-available, P tissue, plant height, wet weight and dry weight of plant and tomato plant production. The application of SP-36 and rock phosphate fertilizer gave an increase to P-available and P-tissue variables, whereas for the production of SP-36 fertilizer plants with dose of 65 g/plant gave higher yield compared to rock phosphate fertilizer.